2014
DOI: 10.1186/preaccept-8338723361312879
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous high-resolution detection of multiple transcripts combined with localization of proteins in whole-mount embryos

Abstract: BackgroundWhole-mount in situ hybridization (WISH) is a fundamental tool for studying the spatio-temporal expression pattern of RNA molecules in intact embryos and tissues. The available methodologies for detecting mRNAs in embryos rely on enzymatic activities and chemical reactions that generate diffusible products, which are not fixed to the detected RNA, thereby reducing the spatial resolution of the technique. In addition, current WISH techniques are time-consuming and are usually not combined with methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 0 publications
1
70
0
Order By: Relevance
“…In situ transcript detection methods are qualitative and describe a transcript domain spatially, but do not provide quantitative data of transcript levels. However, recent advances in quantitative, single-molecule RNA transcript detection offer new possibilities [240242]. For example, there are reports that bmp ligand expression during gastrulation is graded across the ventral half embryo, with highest expression ventrally and lowest expression laterally [144,178], while others do not report a difference in bmp expression [127,128,130,137,243].…”
Section: Current and Emergent Methods Of Spatial And Temporal Manimentioning
confidence: 99%
“…In situ transcript detection methods are qualitative and describe a transcript domain spatially, but do not provide quantitative data of transcript levels. However, recent advances in quantitative, single-molecule RNA transcript detection offer new possibilities [240242]. For example, there are reports that bmp ligand expression during gastrulation is graded across the ventral half embryo, with highest expression ventrally and lowest expression laterally [144,178], while others do not report a difference in bmp expression [127,128,130,137,243].…”
Section: Current and Emergent Methods Of Spatial And Temporal Manimentioning
confidence: 99%
“…In addition to fixation, Gross-Thebing and colleagues (Gross-Thebing et al, 2014) reported that air drying zebrafish embryos for 30 minutes was crucial for maintaining embryo integrity. However, our tests showed that air drying was not necessary to maintain chick embryo integrity (HHSt11-18) and yield strong RNAscope signal.…”
Section: Resultsmentioning
confidence: 99%
“…Our RNAscope protocol for whole chick embryos was based upon published work that was the first to report using the novel RNAscope multiplex fluorescence in situ hybridization technology in a zebrafish embryo model system (Gross-Thebing et al, 2014). Optimization for the chick embryo required us to make several adaptations that are detailed in Suppl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations